The Effect of Combination of Core Stability Training and Lower Extremity Strength Training on Static Standing Balance Ability in a Child with Down Syndrome - Adelia Rahmayanti; Farid Rahman; Intan Herlinawati (Journal of Advanced Multidisciplinary Research, 2022)
Balance is the ability to stay in one position with good control. Children with a diagnosis of Down syndrome usually have decreased muscle tone (hypotonia) or muscle weakness, so that their balance is disturbed and they are more prone to falling when standing. Core stability and lower extremity strength exercise are expected to improve the ability of static standing balance in children with a diagnosis of Down syndrome. The aim of the study is to determine the effect of giving a combination of core stability and lower extremity strength exercises on the static standing balance ability in children with Down syndrome. This study uses a single subject research on a child with a diagnosis of Down syndrome who is given core stability and lower extremity strength exercise for 4 weeks to improve the ability of static standing balance. The ability of static standing balance in this study was measured using Gross Motor Function Measure (GMFM). Measurements were taken before exercise was given (A1), follow-up (B) and final evaluation (A2). After being given exercise twice for four weeks, there was no increase in the GMFM score, so it was concluded that there was no increase in the ability of static standing balance in children with Down syndrome in this study. In conclusions, giving core stability exercise and lower extremity strength exercise twice for four weeks is considered not to be able to improve the ability of static standing balance in children with Down syndrome.